Analisis Pemasaran Jagung sebagai Bahan Pakan Ternak Ayam Ras Petelur di Sumatera Barat - E. Rahmi; B. Arif; T. Perdana (Jurnal Peternakan Indonesia (Indonesian Journal of Animal Science), 2011)
The reseacrh was conducted in West Sumatera. There was a phenomenon in the research area that poultry farmers had difficulty to got maize for feed of egg poultry. The purposed of the reseacrh were to: (1) identify marketing channel of maize, (2) measure and analyze the marketing margin of each distribution channel. Method of the research was qualitative and quantitative description to analyze marketing margin in of each distribution channel. The result of research revealed that : (1) In the West Pasaman 100% maize farmers sold the maize to retailer, 62,5 % of retailers sold the maize to feed industry, 33,3% retailers sold to egg poultry farmers in 50 Kota, and 4,2% retailers sold to local consumers in West Pasaman, meaning that feed industry got the biggest share of maize marketing in West Sumatra, (2) Marketing margin of the first marketing channel was Rp.693.75/kg (26,17%) and farmers’ share was 73,82%, in the second channel Rp.953.33/kg (32,78%) and farmers’ share was 67,13%, and in third channel was Rp.500/kg (20,41%) where the biggest farmers’ share (79,59%), although their were very small. So, the most efficient marketing margin was the first marketing channel.